An evaluation of techniques used in superficial radiotherapy for non-melanoma skin cancer to replicate the planned treatment area: A prospective study. Issue 4 (November 2019) - Vassiliou, M.; Callender, J.; Manning-Stanley, A.S.
Abstract: Introduction: Accuracy of superficial radiotherapy for non-melanoma skin cancer is dependent on replicating the original clinical mark-up. Responses from 18 UK Radiotherapy centres identified the four most common replication techniques; the accuracy and time-efficiency of each was evaluated, as well as participant preference and confidence. Methods: A 2.0  cm × 2.5  cm ellipse field was drawn around the nasal ala of a surrogate patient. Templates for each replication method (1–4) were created, and skin marks removed. Twenty-five therapeutic radiographers used each method to replicate the mark-up. Measurements were recorded for lateral and longitudinal displacement, ellipse diameter and time taken. A post-study questionnaire recorded participant preference and perceived confidence. Results: Comparison of the mean ellipse areas for methods 1–4 identified no statistically significant differences (ANOVA test; p = 0.579 to p = 0.999). Lateral and longitudinal displacements for method 1–4 showed a statistically significant difference between method 3 and each of methods 1, 2, 4 for lateral and longitudinal respectively (ANOVA; lateral: p = 0.008, p = 0.002, p = 0.05; longitudinal: p = 0.036, p = 0.000, and p = 0.000). Mean time taken was longest for method 3, and was compared using a Friedman test (p = 0.000) identifying a statistically significant difference. Twenty-two participants completed the questionnaire. 48% favoured method 2, 41% method 4. Method 3 was least favourite. A Likert scale (1–10) measured confidence. Participants had most confidence in methods 2 and 4. Conclusion: In this study, method 3 was least accurate, most time consuming, and was least favoured by users. The clinical significance of these results will depend on the margins used in local practise. Highlights: Variation exists in replication methods for a superficial radiotherapy technique between treatment centres in the UK. The least accurate and most time consuming method in the study was method 3 (use of annotated photographs). Method 3 was also least preferred by, and instilled the least confidence in, radiographers during the study. Methods 2 (acetate template) and 4 (partial thermoplastic mask) were most preferred and instilled most confidence.